Exploring medical students' perceptions of the flipped classroom model: A cross- sectional study - Aakash kumar; kanza Mehmood; Sadia Rehman; Hasan Ali; Hina Moazzam; Muhammad Faisal Fahim (Journal of University Medical & Dental College, 2026)
BACKGROUND AND OBJECTIVE: The flipped classroom model in medical education is gaining more attention as an innovative way to enhance engagement and active learning. Therefore, this study explores medical students' perceptions of the flipped classroom model and investigates whether preferences change across different years of study at a medical college in Karachi, Pakistan. To explore medical students' perceptions of the flipped classroom model in a medical college in Karachi, Pakistan.METHODOLOGY: This cross-sectional study, conducted at Bahria University Health Sciences Campus, Karachi, included 298 randomly sampled students. Structured questionnaires were used to collect data, and SPSS 23 was used for analysis. Associations (p < 0.05) were evaluated using the Fisher test. All participants provided their informed permission, and ethical approval was obtained.RESULTS: Most students rated their knowledge of the flipped classroom model as average to limited, with significant variations across years of study (p = 0.001). Preferences varied, with 38% of favoring a blended teaching approach, while a traditional lecture-style was more popular among year students. Screen-based educational activities were frequently engaged in by 43.9% of  students, and online resources were the preferred choice for tackling challenging topics, especially among  (76%).CONCLUSION: The flipped classroom is perceived differently by medical students over time, according to research, which highlights the need for flexible teaching strategies that combine traditional and flipped methods to improve academic performance and student engagement.